Strategic Management - Morris, John (Open textbook library., 2023)
This open source textbook is derived from many sources, initially from the Principles of Management by Carpenter, Bauer, and Erdogan, but there is abundant new content as well. It is published under a Creative Commons license and as such there is no charge ever for this textbook. The most important change from 1e is that static content was removed to make room for student-generated dynamic content. Throughout the book look for the names of contributing students in the red colored example boxes. As the term progresses, you will see new examples appear as fellow students research and summarize topics for current events, all are curated by the instructor.